2020
DOI: 10.3390/molecules25081925
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelins Prevent Propagation of Lipid Peroxidation—LC-MS/MS Evaluation of Inhibition Mechanisms

Abstract: Free radical driven lipid peroxidation is a chain reaction which can lead to oxidative degradation of biological membranes. Propagation vs. termination rates of peroxidation in biological membranes are determined by a variety of factors including fatty acyl chain composition, presence of antioxidants, as well as biophysical properties of mono- or bilayers. Sphingomyelins (SMs), a class of sphingophospholipids, were previously described to inhibit lipid oxidation most probably via the formation of H-bond networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Furthermore, the chemical composition of the reactive species generated by the CPP depends on the distance of the plasma source from the target and the type of target [ 43 , 54 ]. Various methods have been developed to study the interaction of reactive species with lipid mono- and bilayers such as infrared reflection absorption spectroscopy (IRRAS) [ 55 ], atomic force microscopy [ 56 , 57 ], electrochemistry [ 58 , 59 , 60 ], and mass spectrometry [ 61 , 62 , 63 ]. Scholz et al introduced an electrochemical assay to quantify the oxidative damage of self-assembled monolayers (SAM) on gold electrodes [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the chemical composition of the reactive species generated by the CPP depends on the distance of the plasma source from the target and the type of target [ 43 , 54 ]. Various methods have been developed to study the interaction of reactive species with lipid mono- and bilayers such as infrared reflection absorption spectroscopy (IRRAS) [ 55 ], atomic force microscopy [ 56 , 57 ], electrochemistry [ 58 , 59 , 60 ], and mass spectrometry [ 61 , 62 , 63 ]. Scholz et al introduced an electrochemical assay to quantify the oxidative damage of self-assembled monolayers (SAM) on gold electrodes [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can inhibit lipid oxidation by the formation of an H-bond network within membranes [100]. Coliva et al (2020) suggested that sphingomyelins might prevent the propagation of lipid peroxidation [101]. According to Crnogaj et al (2015), B. canis infection in dogs is associated with a high concentration of lipid peroxidation [102].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in bioactive sphingolipids are a hallmark of metabolic chronic liver diseases, and the relationship between an increment of ceramide production, lipotoxicity, inflammation, and liver disease has been widely described 44 ; however, the increase in the SM(32:1) observed in the livers of relaxin-2-treated animals was not accompanied by an increase in ceramide hepatic levels, so, in our opinion, it should not be contemplated as an unfavorable effect. Indeed, SM are major components of mammalian cells with important and different physiological or pathological roles determined by the tissue context, by the composition/length of its acyl chains and by its concentration in the cells, 45 where they can also act as biophysical antioxidants 46 preventing lipid peroxidation, an arising central feature in hepatic lipotoxicity. 45 The CD36 receptor is a multifunctional membrane receptor that develops a crucial role in FA uptake and lipid metabolism and homeostasis, as well as in inflammation, and it directly participates in the rate of FA uptake by hepatocytes, being its hepatic expression significantly elevated in animal F I G U R E 4 Changes in the hepatic content of saturated and monounsaturated fatty acids, diglycerides and sphingomyelin in rats treated with relaxin-2.…”
Section: Discussionmentioning
confidence: 99%